Climate change and international trade - Leal-Arcas, Rafael (Cheltenham, UK : Edward Elgar, 2013)
'The insightful book contributes to developing the architecture for a global climate agreement and, in doing so, seeks and proposes new approaches to climate change mitigation by linking it to the international trade system. The author suggests the adoption of a bottom-up approach to climate change negotiations by using the evolution of multilateral trade agreements as a model for reaching a global climate treaty. He discusses the innovative approach of inserting climate goals within regional trade agreements, given their proliferation, especially bilateral, in the international trading system. He explains the trade implications of climate change mitigation policies by analyzing a couple of areas where the international regimes for trade and climate change mitigation may potentially clash'--Provided by publisher
The climate change challenge in the context of international trade -- Environmental protection and the international trade system -- Legal and policy responses to climate change -- Analyzing the Kyoto Protocol -- Top-down and bottom-up approaches to climate change and trade -- Regional trade agreements and climate change -- Geoengineering the climate and possible trade implications.
Includes bibliographical references (p. 472-502) and index.
Keywords: Foreign trade regulation -- Environmental aspects; Climate change mitigation -- Economic aspects; Climate change mitigation -- International cooperation